Efeito inibitório in vitro de miltefosina frente à cepas de histoplasma capsulatum var. capsulatum e sporothrix spp. - Malaquias, Ângela Donato Maia (2013)
istoplasma capsulatum var. capsulatum and Sporothrix spp. are dimorphic fungi, pathogenic, causing histoplasmosis and sporotrichosis, respectively, being able to affect humans and other animals. Although the commonly used antifungal therapy is effective for the treatment of such fungal infections, some drawbacks may be mentioned, as the need for treatment for prolonged periods, as well as by the high toxicity of amphotericin B. Moreover, refractory cases and recurrences have been described. This scenario has driven the search for new agents that have antifungal activity. Some studies have shown that certain drugs already used clinically in the treatment of non-fungal etiology diseases may have significant antifungal potential. The miltefosine, originally developed as anticancer agent and currently used in the treatment of leishmaniasis, has demonstrated a significant antifungal activity against various fungal pathogens. Based on the above, this study aimed to evaluate the antifungal activity in vitro of miltefosine against the dimorphic fungi H. capsulatum var. capsulatum and S schenckii complex species including S. brasiliensis, S. schenckii, S. globosa and S. mexican, by broth microdilution technique standard by CLSI. The results showed that miltefosine inhibitory effect in vitro against H. capsulatum var. capsulatum and Sporothrix spp. being able to inhibit the growth of all strains analyzed. The Minimum Inhibitory Concentration (MIC) values obtained ranged from 0.25 to 2 mg.L-1 for H. capsulatum var. capsulatum the filamentous phase and from 0.125 to 1 ug.mL-1 in the yeast phase. For Sporothrix spp. filamentous phase in the MIC range was from 0.25 to 2 mg.L-1. The Minimum Fungicidal Concentration (MFC) values were ≤ 4 mg L-1 for both species analyzed. Thus, the present study demonstrated for the first time the relevant antifungal activity of miltefosine against H. capsulatum var. capsulatum and Sporothrix spp. It is noteworthy that more studies are necessary to evaluate the applicability of miltefosine in vivo and validate its use as an alternative to support the treatment of patients with histoplasmosis and sporotrichosis.